Keterampilan Berpikir Kritis Ditinjau dari Jenis Kelamin Pada Materi Sistem Pertahanan Tubuh dengan Model Pembelajaran Discovery Learning berbantuan Google Classroom - anggi nopitasari (Jurnal Pendidikan Biologi Undiksha, 2022)
Critical thinking skills are one of the skills that everyone must have to face the challenges of the 21st century. Indonesia's 2018 PISA results are still low with a rank of 72 out of 78 countries where these PISA questions are questions with higher-level thinking skills that cause students' critical thinking skills. Learning model and sex differences are variables that must be considered in an effort to improve critical thinking skills. The purpose of this study was to determine whether there is an effect of Discovery Learning learning model assisted by Google Classroom and sex differences on students' critical thinking skills and to determine whether there is an interaction between learning models and sex differences on students' critical thinking skills on the material of the body's defense system. The results showed that there was no significant difference from the Discovery Learning and Expository Learning learning models assisted by Google Classroom as well as sex differences where the results of the Two WayANOVA Test for the learning model variable were 0.232 and for sex differences 0.270. then there is no significant interaction between the learning model and sex differences on critical thinking skills with a significance value for the interaction between the learning model and sex differences of 0.513.